Lipid nano-carriers loaded with a extract for epilepsy treatment characterization and efficacy studies - Mihailova, Ljubica; Tchekalarova, Jana; Shalabalija, Dushko; Geskovski, Nikola; Stoilkovska Gjorgievska, Veronika; Stefkov, Gjoshe; Krasteva, Paoleta; Simonoska Crcarevska, Maja; Glavas Dodov, Marija (Elsevier BV, 2022)
Taking into consideration the latest reported beneficial anticolvusant effects of cannabidiol (CBD) and cannabiodiolic acid (CBDA) for clinical applications and the advantages of lipid nano-systems as carriers for targeted brain delivery, the aim of this study was set in direction of in vitro physico-chemical and biopharmaceutical characterization and in vivo evaluation of nanoliposomes and nanostructured lipid carriers loaded with Cannabis sativa extract intended for safe and efficient transport via blood-brain barrier and treatment of epilepsy. These nanoliposomes and nanostructured lipid formulations were characterized with z-average diameter <200 nm, following unimodal particle size distribution, negative values for Z-potential, high drug encapsulation efficiency and prolonged release during 24h (38.84-60.91 %). Prepared formulations showed statistically significant higher antioxidant capacity compared to the extract. The results from in vivo studies of the anticonvulsant activity demonstrated that all formulations significantly elevated the latencies for myoclonic, clonic and tonic seizures and, therefore, could be used in preventing different types of seizures. A distinction in the potential of the nano-systems was noted, which was probably anticipated by the type and the characteristics of the prepared formulations.
Keywords: Anticonvulsant activity; Blood-brain barrier; Cannabidiolic acid; Cannabis sativa extract; Epilepsy; Nanoliposomes; Nanostructured lipid carriers.